Collaborative Farming Business Model as Innovative Sustainable Model for Indigenous Chicken Micro-farming: An Economic Perspective - Iffat Abbas ABBASI; Hasbullah ASHARI; Ahmad Shabudin Bin ARIFFIN (Communications of International Proceedings, 2022)
Micro-farming of indigenous chicken livestock is a source of income and food for underprivileged rural households around the world. To survive and cover daily expenses, the underprivileged class in rural places all over the world engages in various agricultural and livestock farming operations. However, these agricultural activities are not long-term enough to help poor farmers earn a consistent income, as outlined in Sustainable Development Goal 2 (SDG 2), which emphasizes the elimination of hunger by promoting sustainable agriculture, supporting small-scale farmers, and providing equal access to land, technology, and markets. Despite the fact that demand for indigenous chicken has grown over time due to the health benefits of eating indigenous chicken. Despite rising demand for indigenous chicken and the potential for indigenous chicken to be a socially viable economic enterprise, marketing and development of indigenous chicken have been hampered by rural poultry constraints. The current study aims to propose collaborative model for indigenous chicken micro-farming. Collaborative business model as an innovative model has been employed in agriculture sector such as dairy industry and sugarcane to integrate supply chain. Collaborative farming model has a potential to overcome issues involved in indigenous chicken micro-farming. The proposed model can be tested using system dynamics modelling.
Keywords: Collaborative Farming; Indigenous Chicken; Sustainable agriculture; Triple bottom line (TBL)